PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR) DAN NET INTEREST MARGIN (NIM) TERHADAP KINERJA KEUANGAN PADA BANK SWASTA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) 2017-2019 - Ni Wayan Riskika Putri; I Wayan Sukadana; I Wayan Suarjana (EMAS, 2022)
A bank is a business entity that collects funds from the community in the form of deposits and distributes them back to the community in the form of credit and or other forms in order to improve the standard of living of the community. Therefore, it is important for banks to maintain public trust because its main activities rely on public trust. This research aims to find out the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM) on the financial performance of Private Banks listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. This study is an associative causal study, which aims to find out the influence of two or more variables. The analysis prerequisite test uses a classical assumption test that includes a normality test, a multicollinearity test, a heteroskedasticity test, and an autocorrelation test. The data analysis method used is multiple regression analysis. The data used in this study is documentation data in the form of financial statements with private bank objects listed on the Indonesia Stock Exchange. Sample collection technique is done using purposive sampling method. Based on existing criteria, 15 banks were obtained who were sampled for research during the period 2017-2019. Based on hypothesis testing using statistical F tests concluded that CAR, LDR, and NIM simultaneously affect ROA. Based on partial test (t) it was concluded that the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) had no significant effect on Return On Asset (ROA) and Net Interest Margin (NIM) had a significant positive effect on Return On Asset (ROA).